Profiling of traditional South African biltong in terms of processing, physicochemical properties and microbial stability during storage - Jones, Maxine Sylvia (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD (Food Sc))--Stellenbosch, 2017.